George and Martha back in town - Marshall, James, 1942- (Boston : Houghton Mifflin, 1984)
Though their friendship is often tested, George and Martha survive with a sense of humor.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
2.5
K-3
Keywords: Children's stories, American; Friendship -- Fiction; Hippopotamus -- Fiction; Friendship -- Fiction; Hippopotamus -- Fiction